WTAP Function in Sertoli Cells Is Essential for Sustaining the Spermatogonial Stem Cell Niche - Jia, Gong-Xue (Stem Cell Reports, 2020)
Sertoli cells are the major component of the spermatogonial stem cell (SSC) niche; however, regulatory mechanisms in Sertoli cells that dictate SSC fate decisions remain largely unknown. Here we revealed features of the N(6)-methyladenosine (m(6)A) mRNA modification in Sertoli cells and demonstrated the functions of WTAP, the key subunit of the m(6)A methyltransferase complex in spermatogenesis. m(6)A-sequencing analysis identified 21,909 m(6)A sites from 15,365 putative m(6)A-enriched transcripts within 6,122 genes, including many Sertoli cell-specific genes. Conditional deletion of Wtap in Sertoli cells resulted in sterility and the progressive loss of the SSC population. RNA sequencing and ribosome nascent-chain complex-bound mRNA sequencing analyses suggested that alternative splicing events of transcripts encoding SSC niche factors were sharply altered and translation of these transcripts were severely dysregulated by Wtap deletion. Collectively, this study uncovers a novel regulatory mechanism of the SSC niche and provide insights into molecular interactions between stem cells and their cognate niches in mammals.